Comparison of Cardiovascular Risk Factors in European Population Cohorts for Predicting Atrial Fibrillation and Heart Failure, Their Subsequent Onset, and Death - Benedikt Schrage; Bastiaan Geelhoed; Teemu J. Niiranen; Francesco Gianfagna; Julie K. K. Vishram‐Nielsen; Simona Costanzo; Stefan Söderberg; Francisco M. Ojeda; Erkki Vartiainen; Maria Benedetta Donati; Christina Magnussen; Augusto Di Castelnuovo; et al. (WILEY, 2025)
Background: Differences in risk factors for atrial fibrillation (AF) and heart failure (HF) are incompletely understood. Aim of this study was to understand whether risk factors and biomarkers show different associations with incident AF and HF and to investigate predictors of subsequent onset and mortality.
Methods and Results: In N=58 693 individuals free of AF/HF from 5 population-based European cohorts, Cox regressions were used to find predictors for AF, HF, subsequent onset, and mortality. Differences between associations were estimated using bootstrapping. Median follow-up time was 13.8 years, with a mortality of 15.7%. AF and HF occurred in 5.0% and 5.4% of the participants, respectively, with 1.8% showing subsequent onset. Age, male sex, myocardial infarction, body mass index, and NT-proBNP (N-terminal pro-B-type natriuretic peptide) showed similar associations with both diseases. Antihypertensive medication and smoking were stronger predictors of HF than AF. Cholesterol, diabetes mellitus, and hsCRP (high-sensitivity C-reactive protein) were associated with HF, but not with AF. No variable was exclusively associated with AF. Population-attributable risks were higher for HF (75.6%) than for AF (30.9%). Age, male sex, body mass index, diabetes mellitus, and NT-proBNP were associated with subsequent onset, which was associated with the highest all-cause mortality risk.
Conclusions: Common risk factors and biomarkers showed different associations with AF and HF, and explained a higher proportion of HF than AF risk. As the subsequent onset of both diseases was strongly associated with mortality, prevention needs to be rigorously addressed and remains challenging, as conventional risk factors explained only 31% of AF risk.